2013
DOI: 10.1007/s12640-013-9390-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Preconditioning Alleviates Ethanol Neurotoxicity: The Involvement of Autophagy

Abstract: Ethanol is a neuroteratogen and neurodegeneration is the most devastating consequence of developmental exposure to ethanol. A sublethal preconditioning has been proposed as a neuroprotective strategy against several central nervous system (CNS) neurodegenerative diseases. We have recently demonstrated that autophagy is a protective response to alleviate ethanol toxicity. A modest hypoxic preconditioning (1% oxygen) did not cause neurotoxicity but induced autophagy (Tzeng et al., 2010). We therefore hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…For example, a reduction of SQSTM1 correlates with the induction of mitophagy in murine liver and in primary hepatocytes after alcohol (Ding et al, 2010). Our results are in agreement with previous studies using a variety of cell types subjected to starvation, hypoxia or EtOH (Pursiheimo et al, 2009, Wang et al, 2013, Kuma et al, 2004). In contradistinction, other studies report that EtOH increases SQSTM1 levels in mouse liver, HepG2 cells, and heart muscle cells (Thomes et al, 2015, Guo and Ren, 2012).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…For example, a reduction of SQSTM1 correlates with the induction of mitophagy in murine liver and in primary hepatocytes after alcohol (Ding et al, 2010). Our results are in agreement with previous studies using a variety of cell types subjected to starvation, hypoxia or EtOH (Pursiheimo et al, 2009, Wang et al, 2013, Kuma et al, 2004). In contradistinction, other studies report that EtOH increases SQSTM1 levels in mouse liver, HepG2 cells, and heart muscle cells (Thomes et al, 2015, Guo and Ren, 2012).…”
Section: Discussionsupporting
confidence: 94%
“…Accumulating evidence indicates that alterations in phosphorylation and/or interaction of BECN1 and PIK3C3 are required for stress-induced autophagy (Kim et al, 2013). In the present study, EtOH-induced changes in BECN1 phosphorylation were associated with elevations in autophagy, as indicated by increased LC3B-II (Russel et al, 2013) and decreased SQSTM1 (Ding et al, 2010, Pursiheimo et al, 2009, Wang et al, 2013). The important role of BECN1 in EtOH-induced autophagy is further supported by the observation that knockdown of BECN1 blocked the EtOH-induced changes in LC3B, and SQSTM1.…”
Section: Discussionsupporting
confidence: 55%
“…Taken together, our observations emphasize that a disturbance in the cellular housekeeping, induced by alcohol exposure, can trigger the pro-inflammatory sensor NLRP3, therefore stimulating inflammatory reactions in pluripotent stem cells as well as NPCs. Evidence indicates that multiple factors play a role in the alcohol-mediated response, such as Heat Shock Factor 1 [ 53 ], mTOR [ 54 , 55 ], or TLR4 [ 6 ]. Though a linear cascade of events has not yet been determined due to the concurrence of multiple cross-talking mechanisms, we have illustrated that an impairment of mitochondrial and lysosomal distribution and function are involved in ethanol-mediated induction of the inflammasome pathway, resulting in a disequilibrium of the innate immune response and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This hypoxic preconditioning protects neuronal cells against ethanol-induced cell death. 44 Inhibition of autophagy blocks hypoxic preconditioning-mediated protection, whereas activation of autophagy enhances neuroprotection caused by hypoxic preconditioning. 41 During development, there is a temporal susceptibility to ethanol neurotoxicity.…”
Section: Autophagic Protection Against Ethanol-mediated Neuronal Damagementioning
confidence: 99%
“…22,108 We have recently shown that rapamycin protects neurons against thiamine deficiency-induced neurodegeneration 109 ; in vitro studies indicate that rapamycin alleviates ethanol-induced death of neuronal cells by activating autophagy. 35,44 Similarly, rapamycin mitigates ethanol-induced liver pathogenesis. 52 In an animal model of ethanol-induced cardiac defect (in which autophagy plays a negative role), however, rapamycin exacerbates ethanol-induced cell injury in cardiomyocytes.…”
Section: Autophagy As a Potential Therapeutic Target For Treating Ethmentioning
confidence: 99%